OC-039 Improving the Quality of Care and Reducing Costs of IBD Patients on Biologic Therapy Through a Multi-Disciplinary Biologics Clinic. (17th August 2016) - Eliadou, E; Reid, V; Kirkbride, M; Brooks, J; Birchall, F; Kemp, K; Levison, S
Abstract : Introduction: NICE IBD quality standard (QS81) and the IBD Standards aim to deliver high quality and safe clinical care to IBD patients throughout the UK that is patient-centred and evidence based. These aims are supported by the national biologic therapy audit. To improve and standardise the care of our IBD patients on biologic therapy we began a weekly multi-disciplinary (physicians, IBD nurses, and pharmacist) virtual biologics clinic (VBC). Here, the response to therapy is monitored (clinical scoring, well-being, laboratory results), the scheduling of investigations are coordinated, and the review and writing of prescriptions undertaken. Methods: We prospectively collected data from our VBC for 8 consecutive weeks. Changes to therapy on clinical grounds were noted, and the financial implications of these changes calculated. Calculations for IFX savings were based on an average dose of 300 mg per patient plus infusion costs. The ordering of required investigations and the occurrence of adverse clinical events were recorded. Results: In 8 weeks, 360 patient reviews were performed relating to 327 patients (IFX = 207, ADA = 79, VEDO = 41). Therapy was adjusted in 41/327 patients (12.5%). 5 stopped biologic therapy, 19 switched drug, 10 reduced and 7 increased therapy frequency. Net saving in prescribing was £10, 928 at 8 weeks (>£65 K/annum). The coordinated prescribing of medication and pharmacy sign off improved the delivery of therapy and patient satisfaction. 23 colonoscopies, 9 MR scans, and 45 outpatient appointments to assess response to therapy at 3 or 12 months, were scheduled from the VBC. 5 complications were highlighted (recurrent infection; 2 required surgery; cancer; severe IBD flare requiring hospitalisation). In total 118/357 (36%) patients had their care altered by VBC intervention (41 adjusted therapies, 77 scheduled monitoring and further clinical input. Conclusion: The VBC provides a safe platform to initiate and monitor biologic therapies and to audit practices. The introduction of a multi-disciplinary VBC has altered the management of 118/327 patients (36%) based on clinical findings, results, and NICE guidance. Significant financial savings (£65 K per annum), the streamlining of prescribing, and superior patient monitoring have helped to improve the quality and safety of care provided. The transition to biosimilar anti-TNF therapies can also be facilitated using a VBC forum. Disclosure of Interest: None Declared